2006
DOI: 10.1007/s10528-006-9040-3
|View full text |Cite
|
Sign up to set email alerts
|

Population Research of Genetic Polymorphism at Amino Acid Position 631 in Chicken Mx Protein with Differential Antiviral Activity

Abstract: A single amino acid substitution between Asn and Ser at position 631 in the chicken Mx protein has been reported to determine resistant and sensitive antiviral activity. In this study, we investigate whether various kinds of chicken breeds and jungle fowls carry the resistant or sensitive Mx allelic gene by using the mismatched PCR-restriction fragment length polymorphism (RFLP) technique. In total, 271 samples from 36 strains of 17 chicken breeds and from 3 kinds of jungle fowls were examined. The rates of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 25 publications
6
35
1
Order By: Relevance
“…Results have shown that mice carrying the MX1 gene with a large deletion or a nonsense mutation are influenza virus-susceptible, have decreased metabolic stability of MX1 mRNA, and lack the ability to synthesize the MX1 protein (Staeheli et al 1988). A single amino acid substitution between Asn and Ser at position 631 in the chicken MX1 protein has been reported to determine resistant and sensitive antiviral activity (Seyama et al 2006;Wang et al 2012). In our study, the g. 143196228 G>A mutation leads to a substitution of arginine to histidine at position 419 in predicted N-terminal GTPase domain, which might alter the MX1 function and regulate the activity of GTPase.…”
Section: Discussionmentioning
confidence: 99%
“…Results have shown that mice carrying the MX1 gene with a large deletion or a nonsense mutation are influenza virus-susceptible, have decreased metabolic stability of MX1 mRNA, and lack the ability to synthesize the MX1 protein (Staeheli et al 1988). A single amino acid substitution between Asn and Ser at position 631 in the chicken MX1 protein has been reported to determine resistant and sensitive antiviral activity (Seyama et al 2006;Wang et al 2012). In our study, the g. 143196228 G>A mutation leads to a substitution of arginine to histidine at position 419 in predicted N-terminal GTPase domain, which might alter the MX1 function and regulate the activity of GTPase.…”
Section: Discussionmentioning
confidence: 99%
“…Recently this SNP have been demonstrated to confer more resistance in chicken to in vivo experimental infection of highly pathogenic avian influenza virus (HPAIV) (Ewald et al, 2011, Wang et al, 2012, Fulton et al, 2014. SNP at 2032 have been analyzed in various chicken breeds (Li et al, 2006, Seyama et al, 2006, Balkisson et al, 2007. However Indian native chicken breeds are yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the allele frequency of the Mx 2032 G/A polymorphism in the chicken using a variety of methods: mismatched polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) (Seyama et al, 2006), electrophoresis of PCR products on polyacrylamide gels (Li et al, 2006), and sequencing (Balkissoon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…New primers and PCR-RFLP protocol were established. The latter PCR-RFLP-based genotyping protocol that does not require the creation of mismatches (Seyama et al, 2006) is here described.…”
Section: Introductionmentioning
confidence: 99%